The Joachim Quartet playing Beethoven - Schmutzer, Ferdinand, 1870-1928 (artist):::Creator:::::::::::: (2020)
Drypoint etching of the Joachim Quartet playing the "Razumovsky" Quartet, op. 59, no. 3, by Beethoven. The members include Joseph Joachim (first violin), Carl Halir (second violin), Emanuel Wirth (viola), and Robert Hausmann (cello).